Examining the Local People's Awareness of Plateau Tourism: The Example of Aydın Province (Third Sector Social Economic Review, 2025)
The economic benefits provided by the tourism sector and changes in tourists' expectations have directed all destinations towards alternative tourism sources beyond the classical sea-sun-sand concept. Plateau tourism is also among the important options within the scope of alternative tourism for tourists. Aydin province is one of Turkey's leading tourism destinations. Although tourism is one of the most important sources of income in the province, there are no studies in the literature focusing on the plateaus of Aydın. In this context, the aim of the research is to reveal the awareness of the local people about plateau tourism. The research aims to contribute to the literature as well as to fulfil the function of introducing the plateaus. A descriptive survey form was prepared regarding the 9 plateaus on the website of the Aydın Provincial Directorate of Culture and Tourism. The universe of the research consists of local people living in Aydın. Convenience sampling method, one of the non-probability sampling types, was preferred for the sample that would represent the universe. In this regard, 430 people were reached face to face and analyses were conducted on 407 valid survey forms. As a result of the analysis, it was revealed that the local people were aware of the Paşa Plateau, Kahvecidere Plateau, Kavşit Plateau and Madran Plateau, while the other plateaus were unknown to the local people. It is evident that plateaus are generally learned about from friends and relatives, and that there is a lack of planned promotion in this regard. As a result of the research, various recommendations were made to local governments and policymakers.
Keywords: Plateu; Plateau Tourism; Local People; Aydın